Crosstalk between non-coding RNAs and programmed cell death in colorectal cancer: implications for targeted therapy - Seyed Reza Taha; Mehdi Karimi; Bahar Mahdavi; Milad Yousefi Tehrani; Ali Bemani; Shahriar Kabirian; Javad Mohammadi; Sina Jabbari; Meysam Hushmand; Alireza Mokhtar; Mohammad Hossein Pourhanifeh (Epigenetics & Chromatin)
Abstract Background Colorectal cancer (CRC) remains one of the most common causes of cancer-related mortality worldwide. Its progression is influenced by complex interactions involving genetic, epigenetic, and environmental factors. Non-coding RNAs (ncRNAs), including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), have been identified as key regulators of gene expression, affecting diverse biological processes, notably programmed cell death (PCD). Objective This review aims to explore the relationship between ncRNAs and PCD in CRC, focusing on how ncRNAs influence cancer cell survival, proliferation, and treatment resistance. Methods A comprehensive literature analysis was conducted to examine recent findings on the role of ncRNAs in modulating various PCD mechanisms, including apoptosis, autophagy, necroptosis, and pyroptosis, and their impact on CRC development and therapeutic response. Results ncRNAs were found to significantly regulate PCD pathways, impacting tumor growth, metastasis, and treatment sensitivity in CRC. Their influence on these pathways highlights the potential of ncRNAs as biomarkers for early CRC detection and as targets for innovative therapeutic interventions. Conclusion Understanding the involvement of ncRNAs in PCD regulation offers new insights into CRC biology. The targeted modulation of ncRNA-PCD interactions presents promising avenues for personalized cancer treatment, which may improve patient outcomes by enhancing therapeutic effectiveness and reducing resistance.